Annamika. - Annamika; Milestone Entertainment; EMI (Malaysia). (Mumbai, India : Milestone Entertainment, 1998)
Contains eight tracks in Punjabi language by popular Indian pop singer Annamika.
CD 1 : Intezaar / (4:57) -- Kala-Sha-Kala / (4:06) -- Aaja Aaja / (4:16) -- One Life To Live / (4:48) -- Punjabi Boliyan / (4:40) -- Oh Oh Oh / (4:30) -- Dil Deewana / (4:45) -- Nindra / (5:26).
Koleksi Khas Wiramanja.
Title from disc label.
Keywords: Songs, Hindi